Imagen corporativa del Gobierno Autónomo Descentralizado de la Parroquia Pimocha - Jiménez Guerra, Carmen Isabel (2019)
The present case study was carried out in the Autonomous Decentralized Rural Parish Government of Pimocha, whose main function is to: Promote investment in works for the benefit of all citizens. The criteria of the qualitative research methodology associated with the inductive method were used for the relevant analysis of the information concerning the factors that affect the corporate image of the GAD. Rural Parish. Based on the collection of information from the survey, it was possible to obtain as a result that citizens qualify as regulating the management of this public institution given that the demands and requests for works by the residents are not heard. In addition, the institution does not have a public relations department